The Use of Short Stories as Materials for Basic Reading Classes for English Language Education Study Program at Universitas Ekasakti - Sherly Franchisca (Jurnal Ilmiah Pendidikan Scholastic, 2021)
Basic reading is conducted to the first semester of English Language Education Study Program at Universitas Ekasakti Padang. There are several text which could be used to in teaching and learning process. One of them are short stories as the proper one for first semester students. By using short stories, the students could enhance their vocabularies and their undertanding in reading text. Besides, there is also moral value that they could get from the text. Throught those, classroom action research about the use of short stories for Basic Reading class were done for the students which the data were taken from tests, observations, interviews and documentation. Sample of the research were consist of 2 (two) classes of the students. as the result, mean score indicate there is an enhancement during the teaching and learning by using short stories. Using short stories in basic reading class is a very good way and also exciting.